Gillnet selectivity for Luciobarbus esocinus (Heckel, 1843) in Keban Dam Lake, Elazig, Turkey - Yuksel, Fahrettin; Gunduz, Fatih; Demirol, Ferhat (Indian Journal of Fisheries, 2014)
A study was conducted to determine the selectivity of monofilament gillnets with mesh sizes of 50, 60, and 70 mm that are used in Keban Dam Lake for fishing Luciobarbus esocinus (Heckel, 1843). During the study, a total of 394 L. esocinus were caught. Selectivity parameters were estimated using the indirect estimation method developed by Holt (1963). Optimum selection lengths for L. esocinus were calculated to be 36.61, 43.94 and 51.26 cm for gillnets with mesh sizes of 50, 60, and 70 mm, respectively. Common selectivity factor was estimated to be 7.32, with standard deviation 4.58. Length at first maturity of female L. esocinus (50 cm) was compared to the optimum selection lengths of gillnets with mesh sizes of 50, 60, and 70 mm. Results indicate that gillnets with mesh size of 70 mm would be appropriate for harvesting L. esocinus in the Keban Dam Lake, as the optimum selection length (51.26 cm) is greater than length at first maturity.